An immersive virtual reality communication skills training for dietitians: A feasibility study - Ivan Moser; Victoria Mirata; Per Bergamin (Elsevier, 2024)
Objective: The training of dietitians emphasizes the development of strong communication skills. Immersive virtual reality (IVR) has been successfully employed for various healthcare scenarios; however, it is yet understudied in dietetics education. Therefore, we conducted a feasibility study to investigate the usefulness of IVR for the purpose of communication skills training. Methods: We designed a multi-user virtual hospital environment that enabled the training of professional conversations between dietitians and patients. Divided into groups of three, 30 dietetics students participated in a role-play task. Taking a qualitative approach to inquiry, we evaluated how participants assessed the benefits and limitations of the IVR training. Results: Participants appreciated the authenticity of the training environment and mentioned various advantages of IVR (e.g., sense of privacy, better focus on conversation) over traditional modes of instruction. On the other side, participants frequently mentioned that the lack of avatars' facial expressions might present an obstacle for effective communication skills training. Conclusion: IVR enables authentic communication skills trainings for dietitians. Special consideration should be given to providing ample social cues during training. Innovation: The study demonstrates that the promising results from other healthcare professions regarding the usefulness of IVR training also apply to dietetics.